An efficient reversible data hiding approach for colour images based on Gaussian weighted prediction error expansion and genetic algorithm. (2015) - Amsaveni, A.; Vanathi, P.T.
A novel reversible data hiding algorithm for colour images based on Gaussian weighted prediction error expansion is proposed in this paper. By this kind of data hiding, the cover image as well as the embedded data shall be completely restored after extraction of the hidden data on receiver side. This method makes use of correlation among colour channels. The Gaussian weighted prediction error expansion improves the prediction accuracy of one channel by considering the edge information from another channel. The proposed system has been carried out through three major steps: obtain edge information, optimise prediction error and sorting parameters using genetic algorithm, embedding and extraction by shifting the histogram of prediction error. The side information involved for recovering the cover image and the secret payload is also less compared to the conventional schemes, as the proposed method employs a single parameter called location map for both hiding as well as extraction. According to the experimental results, the distortion introduced due to secret payload embedding is alleviated to the minimum and hence the perceptual quality of the embedded image is exceptional.